Estudo e análise de aplicação do indicador Oee em uma máquina de trituração de baterias no processo de fundição de chumbo - Santos, Fernando Câmara dos (Universidade do Vale do Rio dos Sinos, 2018)
This paper aims to describe a study about the implementation analysis’ method of the Global Equipment Effectiveness (OEE) in a lead smelter company of the battery grinding sector; aiming the improvement of the performance, availability and quality results’ rate in operations, observing the beginning of the process of raw material supplying for the foundry process, having as raw material the waste batteries scrap, grinding them and, by sequencing, the manufacture of alloys and pure lead. This paper reviews the literature related to the concepts of Total Productive Maintenance (TPM), methodology that originated the OEE indicator, analyzing the original model developed by Nakajima (1993). It will be described in this paper how the implementation method process’ was developed and the actions that were carried out in the company. It will be presented a critical analysis about the obtained results after the implementation of OEE method in the battery grinding equipment during the study period. Obtaining as results an increase of 7.62% in the average Productivity, an average increase of 8% of OEE, consequently a reduction of 17% in the average of unscheduled stops, analysis period from 2015 to 2018.
Keywords: Eficiência global; OEE (Overall Equipment Effectiveness); Manutenção; TPM (Total Productive Maintenance).; Global efficiency; Maintenance